Ectoparasite Detection Of Trichodina Sp In Dumbo Catfish (Clarias gariepinus) In Batu Kumbung Fish Seeds, Lingsar District, West Lombok Regency - Sumarni sumarni; Dina Oktaviana (Mandalika Veterinary Journal, 2022)
The Batu Kumbung Fish Seed Center (BBI) is such an installation and is under the auspices of the Marine and Fisheries Service of West Nusa Tenggara Province, which was established in 1959, which is located in Batu Kumbung Village, Linggsar District, West Lombok Regency. The problem that is often experienced by fish farmers is the emergence of disease attacks, one of which is Trichodina sp. The purpose of this study was to detect the presence of Trichodina sp ectoparasites in catfish (Clarias gariepinus) at the Fish Seed Center (BBI) Batu Kumbung, Lingsar District, West Lombok Regency. This research is a descriptive research type with a survey study type. The research sample was taken using random sampling from five different pool plots in (BBI) Batu Kumbung, Lingsar District, West Lombok Regency. The samples of this study were 15 samples of African catfish (Clarias gariepinus). Examination of the sample using scraping and biopsy. The results of the examination showed that from 15 samples of catfish, 8 positive samples of Trichodina sp. on the gills and obtained 7 positive samples of Trichodina sp. on mucus. Trichodina sp. It has denticles on the surface of its body, its shape is round like a disc and its locomotion is cilia on the outer surface of its body